Exploring residential minimum night consumption in a real water distribution network based on smart-meter data - Alassio, Samuele; Marsili, Valentina; Mazzoni, Filippo; Alvisi, Stefano (Discover water, 2024)
An accurate estimation of leakages in water distribution networks is of primary importance for the definition of strategies aimed at ensuring an efficient management of water resources and avoiding water waste. However, in the case of methods based on water balance—such as the Minimum Night Flow method—inaccurate assessment of the minimum night consumption (MNC), e.g. the assumption of fixed MNC values from the literature, can heavily mislead the quantification of leakage level. This study aims at providing insights into the variability of MNC and the related drivers. In greater detail, hourly water consumption data of approximately 200 users are collected over a period of two years and subjected to a multi-phase methodology to obtain a detailed characterization of MNC, with and without considering the users affected by post-meter leakages. The study demonstrates that factors such as seasonality or the presence of post-meter leakages may strongly impact the MNC—the values of which can significantly deviate from the literature references—and thus lead to significant misestimation of network leakages in water systems. Graphical Abstract Highlights A methodology for the statistical analysis of minimum night consumption (MNC) based on the daily water-consumption profiles at the user level is proposed. The methodology is applied to hourly-resolution water-consumption data collected over two years in a sample of over 200 users. Occupancy rate, seasonality, and presence of post-meter leakages affect MNC statistics.